Leadership under pressure tactics from the front line - Stewart, Bob; IG Publishing (London Philadelphia Kogan Page, 2009)
In Leadership under Pressure, Bob Stewart draws on his experiences in the army and in business, using those experiences to illustrate the key attributes of a leader. In this timely and personal view of leadership, readers learn how to maintain morale in tough times, deal with a crisis, show courage to colleagues, and lead others by example. Stewart's personal experiences including accounts of planning a VIP visit and negotiating with a warlord.
The roots of leadership -- Decision-making tools -- Preparation -- Intelligence -- Innovation -- Planning -- Maintenance of morale -- Personal style -- Tasking -- Supervision -- Courage and example -- Negotiation -- Communication -- Crisis management -- Reflections.
Electronic reproduction.
Keywords: Leadership; Electronic books